Raw frozen Antarctic krill (Euphausia superba) as an alternative feed source for cuttlefish Sepiella japonica in artificial breeding systems. (11th February 2020) - Shi, Huilai; Ping, Hongling; He, Jianyu; Zhang, Tao; Yu, Fangping; Lu, Bin; Liang, Jun; Zhu, Wenbin
Abstract: The study aims to evaluate the feasibility of completely replacing raw frozen shrimp Palaemon gravieri diets with raw frozen Antarctic krill ( Euphausia superba ) in the diets of cuttlefish Sepiella japonica . To address the knowledge gap, we conducted a 60‐day feeding trial. At the end of the experiment (day 60), the cuttlefish Sepiella japonica eating Palaemon gravieri (SJP) grew significantly faster than those eating Euphausia superba (SJE), with the specific growth rate (SGR)SJP (7.92%) > (SGR)SJE (7.09%). Approximately 33.3% and 20.0% mortality was observed in the SJE and SJP, during the course of the experiment respectively. Some important fatty acids (i.e. n‐3 and n‐6 PUFAs) were elevated in SJE with respect to SJP. Replacement of Antarctic krill increased the diversity of the gut microbiome composition in the SJE group. Fluoride accumulated in the ink sac and cuttlebone of cuttlefish in SJE. Overall, these findings imply that PUFA‐rich Antarctic krill could replace P. gravieri shrimp for feeding cuttlefish S. japonica .